Complementary Effects of Two Growth Factors in Multifunctionalized Silk Nanofibers for Nerve Reconstruction. - Kaplan, David, 1953-; Dinis, Tony M.; Vidal, Guillaume.; Jose, Rodrigo R.; Vigneron, Pascale.; Fitzpatrick, Vincent.; Marin, Frédéric.; Egles, Christophe. (Tufts University. Tisch Library., 2016)
With the aim of forming bioactive guides for peripheral nerve regeneration, silk fibroin was electrospun to obtain aligned nanofibers. These fibers were functionalized by incorporating Nerve Growth Factor (NGF) and Ciliary NeuroTrophic Factor (CNTF) during electrospinning. PC12 cells grown on the fibers confirmed the bioavailability and bioactivity of the NGF, which was not significantly released from the fibers. Primary neurons from rat dorsal root ganglia (DRGs) were grown on the nanofibers and anchored to the fibers and grew in a directional fashion based on the fiber orientation, and as confirmed by growth cone morphology. These biofunctionalized nanofibers led to a 3-fold increase in neurite length at their contact, which was likely due to the NGF. Glial cell growth, alignment and migration were stimulated by the CNTF in the functionalized nanofibers. Organotypic culture of rat fetal DRGs confirmed the complementary effect of both growth factors in multifunctionalized nanofibers, which allowed glial cell migration, alignment and parallel axonal growth in structures resembling the 'bands of Bungner' found in situ. Graftable multi-channel conduits based on biofunctionalized aligned silk nanofibers were developed as an organized 3D scaffold. Our bioactive silk tubes thus represent new options for a biological and biocompatible nerve guidance conduit.